A new isoflavone from the fruits of Ficus auriculata and its antibacterial activity. Issue 5 (4th March 2022) - Shao, Tai-Ming; Liao, Hai-Xia; Li, Xiao-Bao; Chen, Guang-Ying; Song, Xiao-Ping; Han, Chang-Ri
Abstract: A new isoflavone ( Z )-5, 7, 4′-trihydroxy-3′-[3-hydroxy-3-methyl-1-butenyl] isoflavone (1 ) together with seven known isoflavones (2–8 ) were isolated from the fruits of the Ficus auriculata . Their structures were established on the basis of 1 D, 2 D-NMR spectroscopic data and HR-ESI-MS analysis. All compounds were evaluated for their antibacterial activities against five pathogenic bacteria in vitro . Compounds 3 and 4 exhibited significant antibacterial activities against five pathogenic bacteria with the MIC values ranging from 1.25 to 20 μg/mL.